Answer:
16
Step-by-step explanation:
(b+5)(b-7)
hope it can help u
Answer:
(a) The solutions are: ![x=5i,\:x=-5i](https://tex.z-dn.net/?f=x%3D5i%2C%5C%3Ax%3D-5i)
(b) The solutions are: ![x=3i,\:x=-3i](https://tex.z-dn.net/?f=x%3D3i%2C%5C%3Ax%3D-3i)
(c) The solutions are: ![x=i-2,\:x=-i-2](https://tex.z-dn.net/?f=x%3Di-2%2C%5C%3Ax%3D-i-2)
(d) The solutions are: ![x=-\frac{3}{2}+i\frac{\sqrt{7}}{2},\:x=-\frac{3}{2}-i\frac{\sqrt{7}}{2}](https://tex.z-dn.net/?f=x%3D-%5Cfrac%7B3%7D%7B2%7D%2Bi%5Cfrac%7B%5Csqrt%7B7%7D%7D%7B2%7D%2C%5C%3Ax%3D-%5Cfrac%7B3%7D%7B2%7D-i%5Cfrac%7B%5Csqrt%7B7%7D%7D%7B2%7D)
(e) The solutions are: ![x=1,\:x=-1,\:x=\sqrt{5}i,\:x=-\sqrt{5}i](https://tex.z-dn.net/?f=x%3D1%2C%5C%3Ax%3D-1%2C%5C%3Ax%3D%5Csqrt%7B5%7Di%2C%5C%3Ax%3D-%5Csqrt%7B5%7Di)
(f) The solutions are: ![x=1](https://tex.z-dn.net/?f=x%3D1)
(g) The solutions are: ![x=0,\:x=1,\:x=-2](https://tex.z-dn.net/?f=x%3D0%2C%5C%3Ax%3D1%2C%5C%3Ax%3D-2)
(h) The solutions are: ![x=2,\:x=2i,\:x=-2i](https://tex.z-dn.net/?f=x%3D2%2C%5C%3Ax%3D2i%2C%5C%3Ax%3D-2i)
Step-by-step explanation:
To find the solutions of these quadratic equations you must:
(a) For ![x^2+25=0](https://tex.z-dn.net/?f=x%5E2%2B25%3D0)
![\mathrm{Subtract\:}25\mathrm{\:from\:both\:sides}\\x^2+25-25=0-25](https://tex.z-dn.net/?f=%5Cmathrm%7BSubtract%5C%3A%7D25%5Cmathrm%7B%5C%3Afrom%5C%3Aboth%5C%3Asides%7D%5C%5Cx%5E2%2B25-25%3D0-25)
![\mathrm{Simplify}\\x^2=-25](https://tex.z-dn.net/?f=%5Cmathrm%7BSimplify%7D%5C%5Cx%5E2%3D-25)
![\mathrm{For\:}x^2=f\left(a\right)\mathrm{\:the\:solutions\:are\:}x=\sqrt{f\left(a\right)},\:\:-\sqrt{f\left(a\right)}\\\\x=\sqrt{-25},\:x=-\sqrt{-25}](https://tex.z-dn.net/?f=%5Cmathrm%7BFor%5C%3A%7Dx%5E2%3Df%5Cleft%28a%5Cright%29%5Cmathrm%7B%5C%3Athe%5C%3Asolutions%5C%3Aare%5C%3A%7Dx%3D%5Csqrt%7Bf%5Cleft%28a%5Cright%29%7D%2C%5C%3A%5C%3A-%5Csqrt%7Bf%5Cleft%28a%5Cright%29%7D%5C%5C%5C%5Cx%3D%5Csqrt%7B-25%7D%2C%5C%3Ax%3D-%5Csqrt%7B-25%7D)
![\mathrm{Simplify}\:\sqrt{-25}\\\\\mathrm{Apply\:radical\:rule}:\quad \sqrt{-a}=\sqrt{-1}\sqrt{a}\\\\\sqrt{-25}=\sqrt{-1}\sqrt{25}\\\\\mathrm{Apply\:imaginary\:number\:rule}:\quad \sqrt{-1}=i\\\\\sqrt{-25}=\sqrt{25}i\\\\\sqrt{-25}=5i](https://tex.z-dn.net/?f=%5Cmathrm%7BSimplify%7D%5C%3A%5Csqrt%7B-25%7D%5C%5C%5C%5C%5Cmathrm%7BApply%5C%3Aradical%5C%3Arule%7D%3A%5Cquad%20%5Csqrt%7B-a%7D%3D%5Csqrt%7B-1%7D%5Csqrt%7Ba%7D%5C%5C%5C%5C%5Csqrt%7B-25%7D%3D%5Csqrt%7B-1%7D%5Csqrt%7B25%7D%5C%5C%5C%5C%5Cmathrm%7BApply%5C%3Aimaginary%5C%3Anumber%5C%3Arule%7D%3A%5Cquad%20%5Csqrt%7B-1%7D%3Di%5C%5C%5C%5C%5Csqrt%7B-25%7D%3D%5Csqrt%7B25%7Di%5C%5C%5C%5C%5Csqrt%7B-25%7D%3D5i)
![-\sqrt{-25}=-5i](https://tex.z-dn.net/?f=-%5Csqrt%7B-25%7D%3D-5i)
The solutions are: ![x=5i,\:x=-5i](https://tex.z-dn.net/?f=x%3D5i%2C%5C%3Ax%3D-5i)
(b) For ![-x^2-16=-7](https://tex.z-dn.net/?f=-x%5E2-16%3D-7)
![-x^2-16+16=-7+16\\-x^2=9\\\frac{-x^2}{-1}=\frac{9}{-1}\\x^2=-9\\\\\mathrm{For\:}x^2=f\left(a\right)\mathrm{\:the\:solutions\:are\:}x=\sqrt{f\left(a\right)},\:\:-\sqrt{f\left(a\right)}\\x=\sqrt{-9},\:x=-\sqrt{-9}](https://tex.z-dn.net/?f=-x%5E2-16%2B16%3D-7%2B16%5C%5C-x%5E2%3D9%5C%5C%5Cfrac%7B-x%5E2%7D%7B-1%7D%3D%5Cfrac%7B9%7D%7B-1%7D%5C%5Cx%5E2%3D-9%5C%5C%5C%5C%5Cmathrm%7BFor%5C%3A%7Dx%5E2%3Df%5Cleft%28a%5Cright%29%5Cmathrm%7B%5C%3Athe%5C%3Asolutions%5C%3Aare%5C%3A%7Dx%3D%5Csqrt%7Bf%5Cleft%28a%5Cright%29%7D%2C%5C%3A%5C%3A-%5Csqrt%7Bf%5Cleft%28a%5Cright%29%7D%5C%5Cx%3D%5Csqrt%7B-9%7D%2C%5C%3Ax%3D-%5Csqrt%7B-9%7D)
The solutions are: ![x=3i,\:x=-3i](https://tex.z-dn.net/?f=x%3D3i%2C%5C%3Ax%3D-3i)
(c) For ![\left(x+2\right)^2+1=0](https://tex.z-dn.net/?f=%5Cleft%28x%2B2%5Cright%29%5E2%2B1%3D0)
![\left(x+2\right)^2+1-1=0-1\\\left(x+2\right)^2=-1\\\mathrm{For\:}\left(g\left(x\right)\right)^2=f\left(a\right)\mathrm{\:the\:solutions\:are\:}g\left(x\right)=\sqrt{f\left(a\right)},\:\:-\sqrt{f\left(a\right)}\\\\x+2=\sqrt{-1}\\x+2=i\\x=i-2\\\\x+2=-\sqrt{-1}\\x+2=-i\\x=-i-2](https://tex.z-dn.net/?f=%5Cleft%28x%2B2%5Cright%29%5E2%2B1-1%3D0-1%5C%5C%5Cleft%28x%2B2%5Cright%29%5E2%3D-1%5C%5C%5Cmathrm%7BFor%5C%3A%7D%5Cleft%28g%5Cleft%28x%5Cright%29%5Cright%29%5E2%3Df%5Cleft%28a%5Cright%29%5Cmathrm%7B%5C%3Athe%5C%3Asolutions%5C%3Aare%5C%3A%7Dg%5Cleft%28x%5Cright%29%3D%5Csqrt%7Bf%5Cleft%28a%5Cright%29%7D%2C%5C%3A%5C%3A-%5Csqrt%7Bf%5Cleft%28a%5Cright%29%7D%5C%5C%5C%5Cx%2B2%3D%5Csqrt%7B-1%7D%5C%5Cx%2B2%3Di%5C%5Cx%3Di-2%5C%5C%5C%5Cx%2B2%3D-%5Csqrt%7B-1%7D%5C%5Cx%2B2%3D-i%5C%5Cx%3D-i-2)
The solutions are: ![x=i-2,\:x=-i-2](https://tex.z-dn.net/?f=x%3Di-2%2C%5C%3Ax%3D-i-2)
(d) For ![\left(x+2\right)^2=x](https://tex.z-dn.net/?f=%5Cleft%28x%2B2%5Cright%29%5E2%3Dx)
![\mathrm{Expand\:}\left(x+2\right)^2= x^2+4x+4](https://tex.z-dn.net/?f=%5Cmathrm%7BExpand%5C%3A%7D%5Cleft%28x%2B2%5Cright%29%5E2%3D%20x%5E2%2B4x%2B4)
![x^2+4x+4=x\\x^2+4x+4-x=x-x\\x^2+3x+4=0](https://tex.z-dn.net/?f=x%5E2%2B4x%2B4%3Dx%5C%5Cx%5E2%2B4x%2B4-x%3Dx-x%5C%5Cx%5E2%2B3x%2B4%3D0)
For a quadratic equation of the form
the solutions are:
![x_{1,\:2}=\frac{-b\pm \sqrt{b^2-4ac}}{2a}](https://tex.z-dn.net/?f=x_%7B1%2C%5C%3A2%7D%3D%5Cfrac%7B-b%5Cpm%20%5Csqrt%7Bb%5E2-4ac%7D%7D%7B2a%7D)
![\mathrm{For\:}\quad a=1,\:b=3,\:c=4:\quad x_{1,\:2}=\frac{-3\pm \sqrt{3^2-4\cdot \:1\cdot \:4}}{2\cdot \:1}](https://tex.z-dn.net/?f=%5Cmathrm%7BFor%5C%3A%7D%5Cquad%20a%3D1%2C%5C%3Ab%3D3%2C%5C%3Ac%3D4%3A%5Cquad%20x_%7B1%2C%5C%3A2%7D%3D%5Cfrac%7B-3%5Cpm%20%5Csqrt%7B3%5E2-4%5Ccdot%20%5C%3A1%5Ccdot%20%5C%3A4%7D%7D%7B2%5Ccdot%20%5C%3A1%7D)
![x_1=\frac{-3+\sqrt{3^2-4\cdot \:1\cdot \:4}}{2\cdot \:1}=\quad -\frac{3}{2}+i\frac{\sqrt{7}}{2}\\\\x_2=\frac{-3-\sqrt{3^2-4\cdot \:1\cdot \:4}}{2\cdot \:1}=\quad -\frac{3}{2}-i\frac{\sqrt{7}}{2}](https://tex.z-dn.net/?f=x_1%3D%5Cfrac%7B-3%2B%5Csqrt%7B3%5E2-4%5Ccdot%20%5C%3A1%5Ccdot%20%5C%3A4%7D%7D%7B2%5Ccdot%20%5C%3A1%7D%3D%5Cquad%20-%5Cfrac%7B3%7D%7B2%7D%2Bi%5Cfrac%7B%5Csqrt%7B7%7D%7D%7B2%7D%5C%5C%5C%5Cx_2%3D%5Cfrac%7B-3-%5Csqrt%7B3%5E2-4%5Ccdot%20%5C%3A1%5Ccdot%20%5C%3A4%7D%7D%7B2%5Ccdot%20%5C%3A1%7D%3D%5Cquad%20-%5Cfrac%7B3%7D%7B2%7D-i%5Cfrac%7B%5Csqrt%7B7%7D%7D%7B2%7D)
The solutions are: ![x=-\frac{3}{2}+i\frac{\sqrt{7}}{2},\:x=-\frac{3}{2}-i\frac{\sqrt{7}}{2}](https://tex.z-dn.net/?f=x%3D-%5Cfrac%7B3%7D%7B2%7D%2Bi%5Cfrac%7B%5Csqrt%7B7%7D%7D%7B2%7D%2C%5C%3Ax%3D-%5Cfrac%7B3%7D%7B2%7D-i%5Cfrac%7B%5Csqrt%7B7%7D%7D%7B2%7D)
(e) For ![\left(x^2+1\right)^2+2\left(x^2+1\right)-8=0](https://tex.z-dn.net/?f=%5Cleft%28x%5E2%2B1%5Cright%29%5E2%2B2%5Cleft%28x%5E2%2B1%5Cright%29-8%3D0)
![\left(x^2+1\right)^2= x^4+2x^2+1\\\\2\left(x^2+1\right)= 2x^2+2\\\\x^4+2x^2+1+2x^2+2-8\\x^4+4x^2-5](https://tex.z-dn.net/?f=%5Cleft%28x%5E2%2B1%5Cright%29%5E2%3D%20x%5E4%2B2x%5E2%2B1%5C%5C%5C%5C2%5Cleft%28x%5E2%2B1%5Cright%29%3D%202x%5E2%2B2%5C%5C%5C%5Cx%5E4%2B2x%5E2%2B1%2B2x%5E2%2B2-8%5C%5Cx%5E4%2B4x%5E2-5)
![\mathrm{Rewrite\:the\:equation\:with\:}u=x^2\mathrm{\:and\:}u^2=x^4\\u^2+4u-5=0\\\\\mathrm{Solve\:with\:the\:quadratic\:equation}\:u^2+4u-5=0](https://tex.z-dn.net/?f=%5Cmathrm%7BRewrite%5C%3Athe%5C%3Aequation%5C%3Awith%5C%3A%7Du%3Dx%5E2%5Cmathrm%7B%5C%3Aand%5C%3A%7Du%5E2%3Dx%5E4%5C%5Cu%5E2%2B4u-5%3D0%5C%5C%5C%5C%5Cmathrm%7BSolve%5C%3Awith%5C%3Athe%5C%3Aquadratic%5C%3Aequation%7D%5C%3Au%5E2%2B4u-5%3D0)
![u_1=\frac{-4+\sqrt{4^2-4\cdot \:1\left(-5\right)}}{2\cdot \:1}=\quad 1\\\\u_2=\frac{-4-\sqrt{4^2-4\cdot \:1\left(-5\right)}}{2\cdot \:1}=\quad -5](https://tex.z-dn.net/?f=u_1%3D%5Cfrac%7B-4%2B%5Csqrt%7B4%5E2-4%5Ccdot%20%5C%3A1%5Cleft%28-5%5Cright%29%7D%7D%7B2%5Ccdot%20%5C%3A1%7D%3D%5Cquad%201%5C%5C%5C%5Cu_2%3D%5Cfrac%7B-4-%5Csqrt%7B4%5E2-4%5Ccdot%20%5C%3A1%5Cleft%28-5%5Cright%29%7D%7D%7B2%5Ccdot%20%5C%3A1%7D%3D%5Cquad%20-5)
![\mathrm{Substitute\:back}\:u=x^2,\:\mathrm{solve\:for}\:x\\\\\mathrm{Solve\:}\:x^2=1=\quad x=1,\:x=-1\\\\\mathrm{Solve\:}\:x^2=-5=\quad x=\sqrt{5}i,\:x=-\sqrt{5}i](https://tex.z-dn.net/?f=%5Cmathrm%7BSubstitute%5C%3Aback%7D%5C%3Au%3Dx%5E2%2C%5C%3A%5Cmathrm%7Bsolve%5C%3Afor%7D%5C%3Ax%5C%5C%5C%5C%5Cmathrm%7BSolve%5C%3A%7D%5C%3Ax%5E2%3D1%3D%5Cquad%20x%3D1%2C%5C%3Ax%3D-1%5C%5C%5C%5C%5Cmathrm%7BSolve%5C%3A%7D%5C%3Ax%5E2%3D-5%3D%5Cquad%20x%3D%5Csqrt%7B5%7Di%2C%5C%3Ax%3D-%5Csqrt%7B5%7Di)
The solutions are: ![x=1,\:x=-1,\:x=\sqrt{5}i,\:x=-\sqrt{5}i](https://tex.z-dn.net/?f=x%3D1%2C%5C%3Ax%3D-1%2C%5C%3Ax%3D%5Csqrt%7B5%7Di%2C%5C%3Ax%3D-%5Csqrt%7B5%7Di)
(f) For ![\left(2x-1\right)^2=\left(x+1\right)^2-3](https://tex.z-dn.net/?f=%5Cleft%282x-1%5Cright%29%5E2%3D%5Cleft%28x%2B1%5Cright%29%5E2-3)
![\left(2x-1\right)^2=\quad 4x^2-4x+1\\\left(x+1\right)^2-3=\quad x^2+2x-2\\\\4x^2-4x+1=x^2+2x-2\\4x^2-4x+1+2=x^2+2x-2+2\\4x^2-4x+3=x^2+2x\\4x^2-4x+3-2x=x^2+2x-2x\\4x^2-6x+3=x^2\\4x^2-6x+3-x^2=x^2-x^2\\3x^2-6x+3=0](https://tex.z-dn.net/?f=%5Cleft%282x-1%5Cright%29%5E2%3D%5Cquad%204x%5E2-4x%2B1%5C%5C%5Cleft%28x%2B1%5Cright%29%5E2-3%3D%5Cquad%20x%5E2%2B2x-2%5C%5C%5C%5C4x%5E2-4x%2B1%3Dx%5E2%2B2x-2%5C%5C4x%5E2-4x%2B1%2B2%3Dx%5E2%2B2x-2%2B2%5C%5C4x%5E2-4x%2B3%3Dx%5E2%2B2x%5C%5C4x%5E2-4x%2B3-2x%3Dx%5E2%2B2x-2x%5C%5C4x%5E2-6x%2B3%3Dx%5E2%5C%5C4x%5E2-6x%2B3-x%5E2%3Dx%5E2-x%5E2%5C%5C3x%5E2-6x%2B3%3D0)
![\mathrm{For\:}\quad a=3,\:b=-6,\:c=3:\quad x_{1,\:2}=\frac{-\left(-6\right)\pm \sqrt{\left(-6\right)^2-4\cdot \:3\cdot \:3}}{2\cdot \:3}\\\\x_{1,\:2}=\frac{-\left(-6\right)\pm \sqrt{0}}{2\cdot \:3}\\x=\frac{-\left(-6\right)}{2\cdot \:3}\\x=1](https://tex.z-dn.net/?f=%5Cmathrm%7BFor%5C%3A%7D%5Cquad%20a%3D3%2C%5C%3Ab%3D-6%2C%5C%3Ac%3D3%3A%5Cquad%20x_%7B1%2C%5C%3A2%7D%3D%5Cfrac%7B-%5Cleft%28-6%5Cright%29%5Cpm%20%5Csqrt%7B%5Cleft%28-6%5Cright%29%5E2-4%5Ccdot%20%5C%3A3%5Ccdot%20%5C%3A3%7D%7D%7B2%5Ccdot%20%5C%3A3%7D%5C%5C%5C%5Cx_%7B1%2C%5C%3A2%7D%3D%5Cfrac%7B-%5Cleft%28-6%5Cright%29%5Cpm%20%5Csqrt%7B0%7D%7D%7B2%5Ccdot%20%5C%3A3%7D%5C%5Cx%3D%5Cfrac%7B-%5Cleft%28-6%5Cright%29%7D%7B2%5Ccdot%20%5C%3A3%7D%5C%5Cx%3D1)
The solutions are: ![x=1](https://tex.z-dn.net/?f=x%3D1)
(g) For ![x^3+x^2-2x=0](https://tex.z-dn.net/?f=x%5E3%2Bx%5E2-2x%3D0)
![x^3+x^2-2x=x\left(x^2+x-2\right)\\\\x^2+x-2:\quad \left(x-1\right)\left(x+2\right)\\\\x^3+x^2-2x=x\left(x-1\right)\left(x+2\right)=0](https://tex.z-dn.net/?f=x%5E3%2Bx%5E2-2x%3Dx%5Cleft%28x%5E2%2Bx-2%5Cright%29%5C%5C%5C%5Cx%5E2%2Bx-2%3A%5Cquad%20%5Cleft%28x-1%5Cright%29%5Cleft%28x%2B2%5Cright%29%5C%5C%5C%5Cx%5E3%2Bx%5E2-2x%3Dx%5Cleft%28x-1%5Cright%29%5Cleft%28x%2B2%5Cright%29%3D0)
Using the Zero Factor Theorem: = 0 if and only if = 0 or = 0
![x=0\\x-1=0:\quad x=1\\x+2=0:\quad x=-2](https://tex.z-dn.net/?f=x%3D0%5C%5Cx-1%3D0%3A%5Cquad%20x%3D1%5C%5Cx%2B2%3D0%3A%5Cquad%20x%3D-2)
The solutions are: ![x=0,\:x=1,\:x=-2](https://tex.z-dn.net/?f=x%3D0%2C%5C%3Ax%3D1%2C%5C%3Ax%3D-2)
(h) For ![x^3-2x^2+4x-8=0](https://tex.z-dn.net/?f=x%5E3-2x%5E2%2B4x-8%3D0)
![x^3-2x^2+4x-8=\left(x^3-2x^2\right)+\left(4x-8\right)\\x^3-2x^2+4x-8=x^2\left(x-2\right)+4\left(x-2\right)\\x^3-2x^2+4x-8=\left(x-2\right)\left(x^2+4\right)](https://tex.z-dn.net/?f=x%5E3-2x%5E2%2B4x-8%3D%5Cleft%28x%5E3-2x%5E2%5Cright%29%2B%5Cleft%284x-8%5Cright%29%5C%5Cx%5E3-2x%5E2%2B4x-8%3Dx%5E2%5Cleft%28x-2%5Cright%29%2B4%5Cleft%28x-2%5Cright%29%5C%5Cx%5E3-2x%5E2%2B4x-8%3D%5Cleft%28x-2%5Cright%29%5Cleft%28x%5E2%2B4%5Cright%29)
Using the Zero Factor Theorem: = 0 if and only if = 0 or = 0
![x-2=0:\quad x=2\\x^2+4=0:\quad x=2i,\:x=-2i](https://tex.z-dn.net/?f=x-2%3D0%3A%5Cquad%20x%3D2%5C%5Cx%5E2%2B4%3D0%3A%5Cquad%20x%3D2i%2C%5C%3Ax%3D-2i)
The solutions are: ![x=2,\:x=2i,\:x=-2i](https://tex.z-dn.net/?f=x%3D2%2C%5C%3Ax%3D2i%2C%5C%3Ax%3D-2i)
Answer: 2 per month
8 per four months
Step-by-step explanation:
I believe the total is $211.27.
After doing multiple searches on the internet, I believe that tax rate is a percentage of the product that is added to the total cost.
9 percent of 193.84 is 17.4456, which rounds up to 17.44, and 17.44 added to 193.84 is 211.27.
<em>Please, if something isn't correct here, don't refrain to tell me, and I will correct my mistake. Thank you.</em>